Alexithymia and The Complexity of Divorce - Karida, Rika Nur; Ar Rasyid, Reza Dwi; Ridlo, Fairuz; Prisnidiawati, Ajeng; Basuki, Shinta Maulydiyah; Nindhita, Pinastikasari; Algristian, Hafid (Indonesian Scientific Publication, 2025)
Divorce is a major psychosocial stressor, particularly for women, and is strongly associated with depression, anxiety, and insomnia. Alexithymia—a personality construct characterized by difficulties in identifying and expressing emotions—may complicate emotional adjustment following divorce. This case report presents a 35-year-old Javanese woman who developed depression, anxiety, and insomnia after divorce, accompanied by alexithymia traits. Data were obtained through psychiatric evaluation, semi-structured interviews, and corroborative information from her psychosocial environment. The patient showed persistent mood swings, sleep disturbance, limited emotional expression, and an externally oriented cognitive style. Her difficulties in emotional processing, combined with sociocultural pressures as a divorced woman, contributed to her psychological burden. This report highlights the need for early screening of alexithymia in divorced women and emphasizes targeted interventions such as emotional awareness training, expressive therapies, and culturally sensitive psychosocial support. Recognition of alexithymia may prevent chronic depression and improve resilience in post-divorce care.